Effectiveness of community-based mangrove management for biodiversity conservation: A case study from Central Java, Indonesia - Ekaningrum Damastuti; Rudolf de Groot; Adolphe O. Debrot; Marcel J. Silvius (Trees, Forests and People, 2022)
Efforts to rehabilitate degraded mangrove ecosystems in Indonesia started in the 1960s and have recently received increased attention. Rehabilitation efforts have been mainly conducted through community-based mangrove management (CBMM) programs, aimed at restoring important services such as food provisioning and coastal protection, and for biodiversity conservation. Our study assessed the effectiveness of CBMM strategies to conserve biodiversity in four adjacent Indonesian coastal villages (Sriwulan, Bedono, Timbulsloko, Surodadi) in Central Java. For this, we used complementary methodologies combining participatory resource mapping, semi-structured interviews, questionnaire-based interviews, field assessments and literature review. This yielded detailed information on mangrove rehabilitation activities, management approaches and the impacts of mangrove rehabilitation on biodiversity in the four villages. Our analysis focussed on mangrove forest structure and diversity and macro invertebrate diversity.The overall comparison of management performance shows a higher achievement of CBMM applied in Bedono in terms of a larger mangrove diversity and net reforestation coverage, also supporting a higher macrobenthic faunal diversity compared to the other villages. The main contributing factors were a) the longer-term funding and maintenance, b) the greater acceptance for protective legislation, c) the higher levels of public support, d) the fact that more species of mangroves were used, e) the much larger spatial scale of mangrove restoration, and f) the presence of additional measures to reduce wave action in highly eroded areas. The results revealed key determinants of success when restoring mangroves for the purpose of biodiversity conservation and the influence of different CBMM approaches.